A historical overview on medical exchanges between China and Vietnam - Chenxue Jiang; Boying Ma (Wolters Kluwer Health/LWW, 2019)
This article reviews the history of transmission and exchange of medicine between China and Vietnam. Systematic textual research found medical activities such as doctor visits, epidemics transmission, exchanges of therapies, import of local herbal, and drug specialties occurred in both countries. Vietnamese traditional medicine was once a truly large-scale system and one of the biggest branches of Chinese medicine abroad in history.